Effect of lactation on energy metabolism in dairy cows from different categories - Celeska Irena, Ulčar I., Stojkovski V., Dovenski T., Mitrov D., Džadžovski I. (Macedonian Veterinary Review, 2010)
The aim of this article was determination of the energy status of Holstein-Friesian cows in three dairy farms in our country. For that purpose, blood samples were taken from three different farms with similar diet for dairy cows. Blood samples were taken from clinically healthy cows, from 2nd to 7th lactation. Several biochemical parameters were measured for determination of the energy status: glucose, non-esterified fatty acids, β-hydroxybutirate (BHB), triacylglycerols and total cholesterol. Total of N=378 samples were taken from multiparous Holstein-Friesian dairy cows from all categories. Cows were divided into three main groups. The group 1 was formed of dry cows, and it was divided into two subgroups: “far from calving” (n=64) and “close up to calving” (n=62). The animals in the group 2 - early lactation cows, were divided into three subgroups as follows: up to 14 days after calving (n=66), up to 60 days after calving (n=63) and up to 100 days after calving (n=62). The group 3 was with cows that were in middle lactation, more than 100 days after calving (n=61). Biochemical parameters were analyzed with standard colorimetric methods, using Sentinel and Randox reagents, on photometer Stat Fax 3300 (Awareness Technology Inc.). These results have shown that dairy cows developed hypoglycemia and early lipolysis (high level of serum NEFA and BHB), during the dry period. The obtained results confirm the ability of the dairy cows for adaptation in various hysiological stages of lactation, but the actual system of feeding does not allow them to achieve their genetic potential. Finally, the evident health problems, occurring as a result of managerial and nutritional errors on the dairy farms, defined as “production diseases” are the most serious cause for decreased production effects.
Keywords: dairy cows, energy balance, transition period, biochemical profi le, production disease